English Teachers’ Strategies in Teaching Listening Comprehension for Senior High School in MAN Serdang Bedagai - Herlina Herlina; Yulia Arfanti; Risnawaty Risnawaty (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
The article deals with the teachers’ strategies in teaching listening comprehension for Senior High School in MAN Serdang Bedagai. The aims at knowing the teachers’ strategies in teaching listening comprehension , the problems are found by the teachers and how they overcome the problems. The research was conducted by using qualitative method. Techniques used to collect the data are observation, taking note and interview . The researcher selected two participants which is the English teacher’s in grade 12th at MAN Serdang Bedagai . The results of the study are The participant one use note-taking strategies and summarizing strategies and the participant two, use the pay attention strategies when deliver the listening theory and when do the listening practice. Based on the research finding, the conclusion is that there are several strategies which used by the English teachers in teaching listening, the strategies are taking note, summarizing and paying attention.